2010
DOI: 10.1007/s00294-010-0302-6
|View full text |Cite
|
Sign up to set email alerts
|

The distribution of inverted repeat sequences in the Saccharomyces cerevisiae genome

Abstract: Although a variety of possible functions have been proposed for inverted repeat sequences (IRs), it is not known which of them might occur in vivo. We investigate this question by assessing the distributions and properties of IRs in the Saccharomyces cerevisiae (SC) genome. Using the IRFinder algorithm we detect 100,514 IRs having copy length greater than 6 bp and spacer length less than 77 bp. To assess statistical significance we also determine the IR distributions in two types of randomization of the S. cer… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
30
0

Year Published

2013
2013
2022
2022

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 28 publications
(31 citation statements)
references
References 69 publications
(109 reference statements)
1
30
0
Order By: Relevance
“…For example, genome-wide bioinformatics surveys have shown that G-quadruplex motifs are conserved across different eukaryotic organisms and enriched in gene promoter regions (25–33). In certain eukaryotes, cruciform sequences are enriched in intergenic regions and are closely clustered at the 3′-ends of genes (34), whereas Z-DNA motifs have been found near their 5′-end (35,36). Importantly, the occurrence of a motif does not imply that the structure has to form in vivo , and in addition, some motifs (cruciform, G-quadruplex) may correspond to formation of structures in mRNA rather than in DNA.…”
Section: Introductionmentioning
confidence: 99%
“…For example, genome-wide bioinformatics surveys have shown that G-quadruplex motifs are conserved across different eukaryotic organisms and enriched in gene promoter regions (25–33). In certain eukaryotes, cruciform sequences are enriched in intergenic regions and are closely clustered at the 3′-ends of genes (34), whereas Z-DNA motifs have been found near their 5′-end (35,36). Importantly, the occurrence of a motif does not imply that the structure has to form in vivo , and in addition, some motifs (cruciform, G-quadruplex) may correspond to formation of structures in mRNA rather than in DNA.…”
Section: Introductionmentioning
confidence: 99%
“…The sequence randomization was performed by the method of Strawbridge et al (2010). Briefly, the nucleotides in the coding regions were collected together and then distributed randomly within all of the coding regions of the genome.…”
Section: Methodsmentioning
confidence: 99%
“…Genome-wide analyses can provide powerful clues toward clarifying the reasons for the existence of IRs with cruciform-forming potential. However, such studies have been limited, and the conclusions almost stay at the stage reporting the regional abundance of these IRs (Lillo et al 2002; Ladoukakis and Eyre-Walker 2008; Strawbridge et al 2010; Du et al 2013). To understand the implications of IRs with cruciform-forming potential in biological functions, more detailed analyses are required.…”
Section: Introductionmentioning
confidence: 99%
“…Inverted repeats are significantly enriched in eukaryotic genomes, suggesting that they are functionally important. 43,62,63 The majority of human inverted repeats are derived from SINEs. 43 These elements should therefore provide the most attractive structural models of mammalian pre-mRNA splicing, alleviating uncertainties in accuracy of RNA secondary structure predictions encountered with typical pre-mRNAs.…”
Section: Discussionmentioning
confidence: 99%